Design of the PERSEO Registry on the management of patients treated with oral anticoagulants and coronary stent. Issue 11 (7th November 2022) - Sciahbasi, Alessandro; Gargiulo, Giuseppe; Talarico, Giovanni Paolo; Cesaro, Arturo; Zilio, Filippo; De Rosa, Salvatore; Talanas, Giuseppe; Tebaldi, Matteo; Andò, Giuseppe; Rigattieri, Stefano; Misuraca, Leonardo; Cortese, Bernardo; et al.
Abstract : Aim: Percutaneous coronary intervention with stent implantation (PCI-S) in patients requiring chronic oral anticoagulant therapy (OAC) is associated with an increased risk of bleeding and ischemic complications. Different randomized studies showed a significant advantage of a double antithrombotic therapy and superiority of direct oral anticoagulant (DOAC) compared with warfarin, but real-world data are limited. Aim is to evaluate the antithrombotic management and clinical outcome of patients with an indication for OAC who undergo PCI-S in a 'real-world' setting. Methods: The multicentre prospective observational PERSEO (PERcutaneouS coronary intErventions in patients treated with Oral anticoagulant therapy) Registry (ClinicalTrials.gov Identifier: NCT03392948) has been designed to enrol patients requiring OAC treated by PCI-S in 25 Italian centres. A target of at least 1080 patients will be followed for 1 year and data on thromboembolic and bleeding events and changes in antithrombotic therapy will be registered. The primary end point is a combined measure of efficacy and safety outcome (NACE), including major bleeding events and major adverse cardiac and cerebral events at 1-year follow-up in patients treated with DOAC (and dual or triple antiplatelet therapy) compared with the corresponding strategies with vitamin K antagonists. A secondary prespecified analysis has been defined to evaluate NACE in dual versus triple antithrombotic therapy after hospital discharge at 1-year follow-up. Conclusion: The PERSEO Registry will investigate in a 'real world' setting the safety and efficacy of DOAC versus warfarin and dual versus triple antithrombotic therapy in patients with indication for oral anticoagulant therapy who undergo PCI-S.